Ultra-Thin Chiral Metasurface-Based Superoscillatory Lens - Li, Jinxing; Yang, Guohui; Yuan, Yueyi; Wu, Qun; Zhang, Kuang (Frontiers in Materials, 2022)
Meatsurface-based superoscillatory lens has been demonstrated effective in finely tailoring the wavefront of light to generate focal spots beyond the diffraction limit in the far-field that capable of improving the resolution of the imaging system. In this paper, an ultra-thin (0.055 λ0) metasurface-based superoscillatory lens (SOL) that can generate a sub-diffraction optical needle with a long focal depth is proposed, which is constructed by ultra-thin chiral unit cells containing two metal split-ring resonators (SRR) with a 90° twisted angle difference cladded on both sides of a 1.5 mm thickness dielectric substrate, with a high linear cross-polarized transmission coefficient around 0.9 and full phase control capability at 11 GHz. Full-wave simulation shows that SOL generates sub-diffraction optical needle within 10.5 GHz to 11.5 GHz, at the center frequency, the focal depth is 281 mm (10.3 λ0) within 105 mm-386 mm, the full width at half maximum (FWHM) is 18.5 mm (0.68 λ0), about 0.7 times of the diffraction limit, generally consistent with the theoretical result. The proposed ultra-thin chiral metasurface-based SOL holds great potential in integrating into practical imaging applications for its simple fabrication, high efficiency, and low-profile advantages.